Sistem Pengupahan Tenaga Kerja Peternakan Sapi Potong CV. Mtr Jaya Abadi - Melly Indah Syafitri (MTU PRESS, 2022)
The purpose of writing this final project is to find out whether the remuneration system of CV. Mtr Jaya Abadi is good and effective, namely by describing the wage system. CV wage system data. Mtr Jaya Abadi was obtained from the results of interviews, observations, and documentation. The results of the description are compared with existing theories so that the merits and weaknesses of the company's wage accounting system can be identified. This study uses descriptive analysis method to analyze the data, which describes the current wage accounting system by outlining the components in it. The results of the data indicate that the wage accounting system that is run is in accordance with the existing wage system theory, so it is said to be good